The contraceptive knowledge, attitudes and practice among women seeking induced abortion in Mitchell's Plain District Hospital, women's health clinic, Western Cape, South Africa - Sobamowo, Samuel Oluwafemi (Department of Public Health and Family Medicine, 2021)
Background: There is an increased awareness among women of child bearing age on the forms of contraceptives in South Africa. Despite this, there has been a steady rise in the number of induced abortions conducted in the country. The aim and objectives of this study was to understand the contraceptive choices of the women requesting termination of pregnancy as well as their knowledge, attitude and practice toward contraceptives in one of the District Hospitals in Western Cape, South Africa. Methods: This was a cross sectional descriptive study which was conducted in Mitchell's Plain District Hospital, among women seeking induced abortion. Women aged 18 years and older seeking elective Termination of Pregnancy were included in the study. Convenience sampling method was used to select the participants women attending the clinic and who were willing to participate. Researcher-administered questionnaires were used as a data collection tool, and the data analyzed using SPSS version 25. Correlation between socio-demographic factors and contraceptive uptake was made using chi-square and Fisher's tests. Results: Most of the participants were between the ages of 26-39 years, single, unemployed and did not have matric education. There was an acceptable knowledge on contraceptives in terms of types, sources and side effects. However, there was low uptake of contraceptives (17%) prior to falling pregnant. The most common barriers to contraceptives use were side effects, no time to visit the clinic and low level of education. Conclusion: Findings from this study showed that awareness and knowledge of contraceptives does not necessarily translate to practice. In the future, it would be worthwhile to conduct a qualitative in-depth study on decision-making and behavior of all women around contraceptives.